Analisis Efisiensi Peginputan Data di Sistem Informasi Rumah Sakit : Studi Kasus Pada SIHA Dan SITB - Putri, Destryana Haryanti; Ariyani, Nurul Dwi (Barongko: Jurnal Ilmu Kesehatan, 2024)
This study aims to discuss the effectiveness of the SIHA & SITB application at the Muhammadiyah Hospital in Bandung, this discussion discusses data input and the difficulty when entering patient data into the SIHA and SITB web such as the server is often down or the internet connection at the hospital is not good enough. The method used for this study, the author uses a case study approach that includes qualitative methods to evaluate the efficiency of data input in SIHA and SITB at the hospital. While the data was obtained through in-depth interviews with system users, including doctors, nurses, and administrative staff. In this study the author found problems with the SIHA and SITB application systems, namely: (1) The SITB and SITB servers are always down so that users have to wait a long time when uploading patient data (2) Internet connection is not overlooked in this case the internet connection at the Muhammadiyah Hospital is not good enough (3) The tools used to upload patient data such as laptops and computers are very inadequate, the computers and laptops used are very slow. Based on the problems that occur above, the researcher tries to provide several suggestions as follows: (1) SIHA and SITB users must always ask the IT department why the server is always down every day and SIHA and SITB must fix the system so that users no longer have to wait long when uploading patient data (2) The hospital must always maintain the internet connection, especially in this digital era, the hospital should have a better internet connection, such as increasing the internet speed (3) The tools used to upload patient data such as computers or laptops must be replaced or updated to a new version so that the effectiveness of using computers or laptops is no longer slow.